Nets for offshore mariculture - Christensen I. (Mediterranean offshore mariculture, 2000)
The development of cage culture systems need to be understood as a function of a number of different structural and operational elements. The design and installation of mooring systems for marine aquaculture units is a very critical element in the establishment of reliable and effective production systems. Based on careful assessment of site conditions, and an appreciation of cage system characteristics and farm operating requirements, suitable mooring specifications may be developed. This process is particularly important for offshore mariculture, where environmental loading may be far more demanding. This paper reviews the engineering aspects of mooring marine aquaculture systems with respect to potential site conditions.
Advanced Course of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Mediterranean Offshore Mariculture', 1997/10/20-24, Zaragoza (Spain)